Effects of Chronic Low Back Pain and Disability on Quadriceps Angle - A Cross Sectional Survey - Shahid Ishaq, Sufian Ahmed, Saad Shafiq, Muhammad Samama Amjad, Kaniz Rabia, Javeria Aslam, Abdul Rahman, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the effects of chronic low back pain and disability on quadriceps angle. Methodology: A descriptive mesuremental study was conducted at Department of Physical therapy Bakhtawar Amin memorial Hospiatl Multan. After taking written informed consent 350 Patients of age 20-40 years with chronic low back pain were taken. Patients with congenital deformity, neuromuscular disorder, spinal cord injury, leg length discrepancy and previous history of knee/hip surgery and meniscal/ligamentous tear were excluded. Oswestry disability index questionnaire and numeric pain rating scale were used to check disability level and pain intensity respectively. Q angle was measured using goniometer in supine lying. Results: The association of pain with disability for male and female were 0.69(P<0.00) and0.79 (P<0.04) respectively. Pearson’s correlation of Q angle with pain and disability of right leg were 0.42(P<0.00) and 0.13(P<0.041), and left leg were 0.43(P<0.000 and 0.27(P0.001) of male. Pearson’s correlation in female of Q angle with pain and disability of right leg were 0.54(P< 0.00) and 0.45(P<0.01) and for left leg were 0.57(P<0.00) and 0.49(P<0.00) respectively. Conclusion: positive association of pain, disability and Quadriceps angle with pain and disability were found. It was found more significant in female than male.